‘Bingkai" Laporan Berita Isu Tanah di Ulu Kiulu, Sabah dan Pengaruhnya ke atas pemilik tanag, pemimpin pendapat, pemilik tanah, SUHAKAM dan Agensi kerajaan Negeri - Syahruddin Ag Ahmad; Fadzilah Majid Cooke; Gaim James Lunkapis; Marja Azlima Omar (Penerbit UM, 2008)
The procedure of applying ‘framing’ technique in producing news content can be analyzed by using three approaches, namely, types of issues reported in local newspapers, news sources and the implicit goals enacted to publish such a news. Editors of local newspapers have a tendency to portray parties involved in land issues. News are framed in two ways. First, the content should display the empowerment of rights amongst landowners. Secondly, to highlight the functions of SUHAKAM, opinion leaders and states government to verify who’s who behind the rules and regulations regarding land issues in Sabah.